Сharging processes and phase states of macroparticles in low-pressure arc discharge - Bizyukov, А.А.; Chibisov, А.D.; Sereda, K.N.; Romashchenko, E.V.; Dimitrova, V. (Вопросы атомной науки и техники, 2013)
The effects of plasma density and ionic charge on the floating potential of the solitary macroparticle (MP) in a low-pressure arc discharge have been investigated. The energy balance has been studied taking into account mutual influence on each other of the charging processes and heating of the MP. The possibility of the evaporation of the MP is shown. У дуговому розряді низького тиску було досліджено вплив густини плазми та заряду іонів на плаваючий потенціал відокремленої макрочастинки (МЧ). Розглянуто енергетичний баланс з урахуванням взаємного впливу один на одного процесів зарядження та розігріву МЧ. Показано можливість випаровування МЧ В дуговом разряде низкого давления исследуется влияние плотности плазмы и заряда ионов на плавающий потенциал уединенной макрочастицы (МЧ). Рассмотрен энергетический баланс с учетом взаимного влияния друг на друга процессов зарядки и разогрева МЧ. Показана возможность испарения МЧ.